2020
DOI: 10.1101/2020.11.20.20235051
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protein phosphatase 2A, complement component 4, and APOE genotype linked to Alzheimer’s disease using a systems biology approach

Abstract: BackgroundRecent reports suggest that the rare apolipoprotein E (APOE) Christchurch mutation and ε2 allele protect against Alzheimer’s disease (AD) pathology by reducing the burden of tau pathology. However, the mechanism(s) underlying the ε2 protective effect linking to tau is largely unknown.MethodsThe role of the ε2 allele in Alzheimer’s disease (AD) was investigated a genome-wide association study (GWAS) for AD among 2,120 ε2 carriers from the Alzheimer Disease Genetics Consortium (ADGC), and then prioriti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…Total RNA-seq studies from brains of AD individuals showed the involvement of the classical complement pathway (CCP) and the phosphorylation of tau to be associated with AD in an APOE genotype-specific manner ( 36 , 37 ). Molecular profiling of the Tg-FDD +/− /ApoE −/− model revealed changes in autophagy, activated microglia, angiogenesis, and vesicle trafficking pathways, with C1q, the first subcomponent of the C1 complex of the CCP of complement activation, as one of the most upregulated genes and Ppp2r5c (the protein phosphatase 2 (PP2) regulatory subunit B'gamma), involved in the dephosphorylation of Tau, as one of the most downregulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA-seq studies from brains of AD individuals showed the involvement of the classical complement pathway (CCP) and the phosphorylation of tau to be associated with AD in an APOE genotype-specific manner ( 36 , 37 ). Molecular profiling of the Tg-FDD +/− /ApoE −/− model revealed changes in autophagy, activated microglia, angiogenesis, and vesicle trafficking pathways, with C1q, the first subcomponent of the C1 complex of the CCP of complement activation, as one of the most upregulated genes and Ppp2r5c (the protein phosphatase 2 (PP2) regulatory subunit B'gamma), involved in the dephosphorylation of Tau, as one of the most downregulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Data for AD‐related neuropathologic traits were obtained from the same source and included Aβ and phosphorylated tau (p‐tau) measured by immunohistochemistry and neurofibrillary tangles (NFT) measured by microscopic examination as described elsewhere (http://www.radc.rush.edu). 13 We also evaluated gene expression data and semi‐quantitative measures of tau pathology (Braak stage) and neuritic amyloid plaques derived from dorsolateral prefrontal cortex tissue obtained from 177 participants (58 autopsy‐confirmed AD cases and 119 controls) of the Framingham Heart Study (FHS) 14,15 . Sample sizes for analyses of each type of omics data are presented in Tables S2 and S3 in supporting information for the ROSMAP and FHS datasets, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Hutterite cohort 13 We also evaluated gene expression data and semi-quantitative measures of tau pathology (Braak stage) and neuritic amyloid plaques derived from dorsolateral prefrontal cortex tissue obtained from 177 participants (58 autopsy-confirmed AD cases and 119 controls) of the Framingham Heart Study (FHS). 14,15 Sample sizes for analyses of each type of omics data are presented in Tables S2 and S3 in supporting information for the ROSMAP and FHS datasets, respectively. Statistical methods used to analyze these data are presented in the supporting information.…”
Section: 2mentioning
confidence: 99%
“…Previous whole transcriptome-wide studies from autopsied brains demonstrate that the classical complement cascade and tau phosphorylation are linked to AD in an APOE genotype-specific manner [14,15]. However, expression profiles associated with AD have not been intensively investigated in the blood and brain from the same individuals, especially separated by the APOE genotype.…”
Section: Introductionmentioning
confidence: 99%